The New and the Living Way: Meditations on the Letter to the Hebrews - Nalkara, Benny (Asian Horizons, 2015)
Joseph Pathrapankal, The New and the Living Way: Meditations on the Letter to the Hebrews, Bangalore: Asian Trading Corporation, 2012.pp. XI + 136, ISBN 978-81-7086-645-9.